Contract of employment : a non-commercial contract - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
Given the fact that the courts are moulding the law to the changing needs of the society, this chapter discusses the development of common law applicable to an employment relationship.The courts have now recognised that a contract of employment is neither concerned with trade or commerce nor with profit but more with psychology and identity elements of the workers, besides economic consideration. They have also recognised employees’ rights in employment to be on the same footing as ‘proprietary rights’, which cannot be aborted save for just cause and excuse.